Monitoring of Diamond Mill Wear in Time Domain during Stone Cutting Using Cutting Force Measurements. (1st February 2009) - Polini, W.; Turchetta, S.
Abstract : The main focus of this study is to verify the possibility to monitor diamond mill wear by measuring the cutting force during stone machining. An ornamental stone was machined on an NC machining centre, retrofitted with a 3-axis dynamometer and data acquisition systems, to investigate the effects of variations in machining parameters. The sensor data include cutting force measurements, further divided into measurable components, such as x, y, and z . Those components were analysed to determine the sensory features that best correlate with diamond mill wear. Tool wear and machining parameters appeared significantly influencing cutting force signals. This suggests that even under the varying cutting conditions involving different values of process parameters, the identified cutting force feature can be used for the reliable and accurate control of diamond mill wear during stone cutting operations.